THE LOCAL FEES AND TAXES IN FORMING REGIONAL BUDGETS: FINANCIAL (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
The article is aimed at strengthening the revenue base of local budgets in the context of the reform of the state financial system in the Republic of Uzbekistan, in particular, at analyzing the role of local taxes and fees. The article studies the theoretical foundations of fiscal decentralization processes, including the concepts of fiscal federalism of economists such as R. Musgrave and W. Oates, in comparison with the modern practice of Uzbekistan